Perencanaan Penentuan Lokasi Pusat Daur Ulang (PDU) di Kecamatan Liang Anggang - Nurazlina Nurazlina; Muhammad Firmansyah; Muhammad Abrar Firdausy; Muhammad Husin (Prodi Teknik Lingkungan Fakultas Teknik Universitas Lambung Mangkurat, 2026)
Pusat Daur Ulang (PDU) is an example of a waste facility from the government to implement awaste reduction policy by processing waste to residual residue. The purpose of this planning is todetermine the location of the PDU construction in Liang Anggang District. The method used in this planning is by distributing questionnaires/participant level (readiness) of the community. Theplanning results show that based on measurements made using the Google Earth application, theplanned location is estimated to have an area of 6,519 m2, with the land area obtained at thatlocation a PDU can be made with service coverage in Liang Anggang District with the conditionthat the PDU location is inside housing and access roads to the location can be passed by truck-type garbage vehicles in one direction. The planned location of the Pusat Daur Ulang (PDU) inLiang Anggang District according to the field survey and calculation results is located on Jln.Makmur, Village of North Landasan Ulin, Liang Anggang District, Banjarbaru City. Keywords: Waste, Waste minimization, Planning.